CALIBRATION OF TRANSMISSION LINE THERMAL MODEL OF THE DYNAMIC THERMAL CURRENT RATING SOFTWARE IN WIDE AREA MEASUREMENTS SYSTEM - SHERFRIZ SHERRY, MUSA (Universiti Malaysia Sarawak (UNIMAS), 2018)
Dynamic Thermal Current Rating (DTCR) is one of the software tools in Wide Area Measurement (WAM) system that has been widely used by many system operators. It is mainly used to calculate the line rating based on measured or predicted weather conditions on overhead transmission lines. However, around five years ago, the accuracy of the DTCR has becoming an issue in Sarawak Energy Berhad (SEB). Hence, this project is intended to study and discuss in detail of the transmission line thermal model of DTCR software. Accordingly, an improved thermal pi (π) model is proposed. The performance of the improved π model will be distinguished with the existing thermal model. The weather factors that bring a substantial impact on the current rating is also considered. Therefore, this research focusses on calibrating the DTCR through phasor measurement in WAM system, as well as the field measured data. The performances analysis of the thermal models are evaluated using Matlab software based numerical analysis.